1966
DOI: 10.1097/00132586-196608000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Effects of Ci-581, a New Dissociative Anesthetic, in Man

Abstract: Pharmacologic actions of CI-581, a chemical derivative of phencyclidine, were determined in 20 volunteers from a prison population. The results indicate that this drug is an effective analgesic and anesthetic agent in doses of 1.0 to 2.0 mg. per kilogram. With intravenous administration the onset of action is within 1 minute and the effects last for about 5 to 10 minutes, depending on dosage level and individual variation. No tachyphylaxis was evident on repeat doses. Respiratory depression was slight and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
4

Year Published

1982
1982
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 1 publication
3
59
0
4
Order By: Relevance
“…[53][54][55][56] More recent studies have confirmed and extended these findings with more modern neurocognitive measures. For example, learning and memory are among the most selectively affected processes in schizophrenia, 57,58 consistent with the critical role played by NMDAR in hippocampal LTP.…”
Section: Cognitive and Neurochemical Effects Of Nmda Blockadementioning
confidence: 89%
“…[53][54][55][56] More recent studies have confirmed and extended these findings with more modern neurocognitive measures. For example, learning and memory are among the most selectively affected processes in schizophrenia, 57,58 consistent with the critical role played by NMDAR in hippocampal LTP.…”
Section: Cognitive and Neurochemical Effects Of Nmda Blockadementioning
confidence: 89%
“…[43][44][45][46][47][48] In the 1970s, the abuse of PCP was frequently associated with psychotic-like responses (for review see 49 ). In retrospective analyses of admission records from PCP-induced adverse reactions, there was little distinction between symptoms presented by these patients and acute psychotic reactions in schizophrenic patients.…”
Section: The Nmda Receptor Hypofunction Hypothesis Of Schizophreniamentioning
confidence: 99%
“…We previously investigated the clinical pharmacological effects of CI-581, now known as ketamine, a noncompetitive N-methyl-D-aspartic acid (NMDA) glutamate receptor antagonist (Domino et al, 1965). Ketamine has analgesic and dissociative anesthetic properties (Reich and Silvay, 1989).…”
Section: Introductionmentioning
confidence: 99%